Direct observation of the Migdal effect induced by neutron bombardment - Difan Yi; Qian Liu; Shi Chen; Chunlai Dong; Huanbo Feng; Chaosong Gao; Wenqian Huang; Xinmei Jing; Lingquan Kong; Jin Li; Peirong Li; Enwei Liang; et al. (Nature, 2026)
Abstract The search for dark matter focuses now on hypothetical light particles with masses ranging from MeV to GeV (refs. 1–12 ). These particles would leave very faint signals experimentally. A potential avenue for enhancing experimental sensitivity to light matter relies on the Migdal effect 13–15 , which involves the detectable ejection of electrons following the instantaneous accelerations of atoms colliding with neutral dark matter. However, although the Migdal effect could be equally generated in controlled experiments with neutral projectiles, a direct experimental observation of this effect is missing, casting doubt on the reliability of detection experiments relying on this effect. Here we report the direct observation of the Migdal effect in neutron–nucleus collisions, achieving a statistical significance of 5 standard deviations, which rests on 6 candidate events selected out of almost 10 6 recorded events. Our experiments have determined the ratio of the Migdal cross-section to the nuclear recoil cross-section to be $${4.9}_{-1.9}^{+2.6}× {10}^{-5}$$ 4.9 − 1.9 + 2.6 × 10 − 5 , in which nuclear recoils exceed 35 keVee and electron recoils span 5–10 keV. These findings are consistent with theoretical predictions. This work resolves a long-standing gap in experimental validation, which not only strengthens the theoretical foundation of the Migdal effect but also paves the way for its application in light dark matter detection.